Penggunaan Media Tayang Lagu untuk Meningkatkan Motivasi dan Hasil Belajar Menulis Cerpen pada Siswa Kelas IX SMP Negeri 1 Banyuputih - Sutomo Sutomo (Jubindo: Jurnal Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2018)
Short story writing ability is one of basic competences mastered by the students at second grade national junior high school 1 Banyuputih. Based on observation, that ability is still in low category. It was because the teacher does not use learning media. This research aims at increasing stundets aility in short story writing by using song presentation media. Method used in this research was class action research by using observation, interwieew, questionnaire and test in collecting data. Data source was fourty students at second grade national junior high school 1 Banyuputih in academic year 2012/2013. The result shows that in pre cycle, it was found that students’ learning past score is only about 55 %, while in first cycle, it becomes 75 %. Besides, in second cycle, students’ past score increase about 90 %